Relasi Kuasa Pemerintah Daerah, Pemerintah Desa dan Lembaga Adat Dalam Pembangunan Kebudayaan Lokal: Studi di Kampung Adat Bena, Desa Tiwuruwu, Kabupaten Ngada, NTT - Bruno Rey Sonby Pantola (CV. Ulil Albab Corp, 2023)
This research analyzes the power relations between the Local Government, Village Government, and Customary Institutions in the development of local culture in Kampung Adat Bena, Tiwuriwu Village, Ngada Regency, NTT. A descriptive qualitative approach method was used with interviews, observations, and documentation studies. The results showed the need for harmonization of customary norms and formal regulations, as well as collaboration between related parties for sustainable preservation of local culture.